GAYA BAHASA PADA KUMPULAN PUISI SALAH PIKNIK KARYA JOKO PINURBO - Arifan, Rizal; Wartiningsih, Agus; Muzammil, Ahmad Rabi’ul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims of analyzing These types of language styles are used to show the soul and personality of the author through the use of language styles. This research uses a stylistic study, descriptive method in the form of qualitative research. The data source of this research is a collection of poetry Salah Piknik by Joko Pinurbo with data in the form of quotations in the form of stanzas or lines. The data collection technique used is a documentary study with the researcher as a data collection tool. The data that has been collected is tested for validity with reader persistence and theoretical triangulation. Based on the results of data collection and analysis, it was found that metaphorical language style in 20 poetry, personification language style in 15 poetry, irony language style in 11 poetry, anaphora language style in 6 poetry, anticlimax language style in 1 poetry, simile language style in 1 poetry, hyperbole language style in 1 poetry and metonymy language style in 5 poetry. This research has a connection to the 2013 curriculum for Indonesian Language and Literature subjects at the high school level, class XII even semester. The results of this study are expected to be used by teachers as teaching materials in schools related to literature learning materials